A JURIDICAL ANALYSIS OF THE LEGAL STATUS OF CHILDREN BORN BEFORE REGISTERED MARRIAGE: A CASE STUDY OF DECISION No. 202/Pdt.P/PA.Pkb - Qodariah Barkah; Azim Ansori; Armasito (Indonesian Journal of Shariah and Justice, 2025)
The petition submitted to the Pangkalan Balai Religious Court under case No. 202/Pdt.P/2023/PA.Pkb sought judicial clarification regarding the legal status of a child born prior to the formal registration of the parents' marriage. The study explored how the status of such children is determined and examined the judge's reasoning in this case. Using an empirical approach with qualitative data from interviews, documentation, and literature reviews, the research found that the child was declared legitimate as no one contested the child's status as the petitioner's, with witnesses supporting the claim. In reaching its decision, the court took into account the validity of the unregistered marriage based on Islamic legal principles, supported by witness statements, while also emphasizing the safeguarding of the child's rights and placing paramount importance on the child's best interests.